Analisis Kebutuhan Pengembangan E-LKPD Matematika Pada Materi FPB dan KPK Kelas V Sekolah Dasar - Ni Luh Putu Ani Lestiani; I Putu Suardipa; I Komang Wahyu Wiguna (Jayapangus Press, 2026)
Mathematics learning on Greatest Common Factor (GCF) and Least Common Multiple (LCM) in elementary schools still faces several problems, particularly in conceptual understanding, procedure selection, and word-problem solving. This study aimed to describe the condition of GCF and LCM learning, analyze teachers’ and students’ needs, and explain the urgency of developing mathematics electronic student worksheets (E-LKPD) for fifth-grade elementary students. This study employed a descriptive qualitative approach. The data sources included fifth-grade teachers, fifth-grade students, and learning achievement documents from six elementary schools in Cluster I of Baturiti District, namely SD Negeri 1 Baturiti, SD Negeri 3 Baturiti, SD Negeri 4 Baturiti, SD Negeri 1 Bangli, SD Negeri 2 Bangli, and SD Negeri 3 Bangli. Data were collected through observation, interviews, questionnaires, and documentation studies, then analyzed through data reduction, data display, and conclusion drawing. The findings showed that mathematics learning remained teacher-centered, teaching materials were limited to textbooks and written exercises, and students had not received sufficient active, visual, and gradual learning experiences. The achievement of learning objectives in GCF and LCM material reached only 58%, indicating that students’ learning outcomes were not yet optimal and needed stronger instructional support. Teachers and students needed E-LKPD containing clear instructions, concise material summaries, varied examples, gradual exercises, contextual word problems, interactive activities, and attractive visual displays. Therefore, developing mathematics E-LKPD is necessary as a learning solution aligned with field needs, supporting technology integration, increasing student engagement, and strengthening students’ conceptual understanding of mathematics.